Medical home primary care components and current educational service use in children and youth on the autism spectrum - Rizk, Sabrin; Benevides, Teal W.; Shiu, Chengshi Amory; Berg, Kristin L.; Khetani, Mary A. (Frontiers in Education, 2023)
Abstract Introduction: Children and youth on the autism spectrum and their families use health and educational services to address their complex needs. They use primary health care services in the medical home, as endorsed by the American Academy of Pediatrics (AAP). They can also use educational services for their cognitive, social, and adaptive skill development, beginning in early intervention and through their transition to postsecondary or vocational roles. Medical and educational services are organized and delivered in separate systems, thereby placing the primary responsibility for coordinating these services on their families. Methods: Pooled data from the 2016 through 2019 National Survey of Children’s Health was used to measure the association between current educational service use and six medical home primary care components, controlling for select sociodemographic and clinical factors in children and youth on the autism spectrum (n = 1,922). Results: After controlling for select sociodemographic and clinical factors, difficulty getting referrals (aOR= 2.93, 95% CI [1.33, 6.41], P =.007) and no shared decision-making in the medical home (aOR= 2.93, 95% CI [1.21, 7.06], P= .016) resulted higher likelihood of current educational service use. Older children had lower likelihood of current educational service use (aOR= 0.91, 95% CI [0.85, 0.97], P= .003), whereas higher autism severity increased the likelihood of current educational service use (aOR= 1.80, 95% CI [1.10, 2.95], P= .019). Conclusion: Children and youth on the autism spectrum, especially those with moderate or severe autism, had a higher likelihood of education service use, unless they were older, had difficulty getting referrals, and no shared decision-making. Further study is needed for improving the medical home referral or shared decision-making pathways and to identify caregiver strategies for navigating educational systems.